Small survivors: description of two new species of Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) from the Brazilian state of Mato Grosso do Sul - Nascimento, Francisco Eriberto De L.; Santos-Silva, Antonio; Flechtmann, Carlos Alberto Hector (Zootaxa, 2021)
Due to intense human activities in the last decades, many native areas of the Brazilian state of Mato Grosso do Sul were devastated to make way for agriculture and livestock. While necessary for the country’s economy, these changes threaten endemic species, including those that have not yet been described. The identification of new species contributes to conservation policies, and here we described two new species from the Brazilian state of Mato Grosso do Sul: Urgleptes monnei and U. nutrix. Additionally, Atrypanius lineatocollis (Bates, 1863) is newly recorded for Mato Grosso and Mato Grosso do Sul.